PENTINGNYA BERPIKIR ANALITIS DALAM KEBERHASILAN PEMECAHAN MASALAH PADA PEMBELAJARAN IPA - Swastika, Ardiani Prameswari; Agustin, Mayang Nabila; Aini, Nabila; Jariyah, Ita Ainun (Universitas Tanjungpura, 2024)
Knowledge in learning is not enough to become a deep learner facing developments over time. Learning needs to meet the skills demands of the century 21 like problem solving. Problem solving is the ability to find a way get out of a problem. The provision of analytical thinking can help solve problems such as gathering and analyzing information. This is really needed in the world education, especially science learning. This research aims to find out the importance of analytical thinking in successful problem solving in science learning. The type of research used is a literature review with a qualitative approach. Technique data collection utilized literature studies from national journals and international journals which is relevant. The data analysis technique used is a content analysis technique. Truth data tested by optimizing research tenacity. The results show that learning science is closely related to problem solving and critical thinking abilities one of the factors of success. Learning models that can support analytical thinking and problem solving ability is problem based learning, hypothetical learning cycle deductive, discovery learning, guided discovery model and RICORSE.